Legal Solutions to Street Sexual Harassment in the #MeToo Era - Brunsdon, Denise (Atlantis)

(untitled) (Mount Saint Vincent University, 2018)
Street sexual harassment is the unwelcome commoditization of women’s bodies by fellow citizen-strangers. This harm is under-recognized by traditional, Anglocentric common law. This paper begins by discussing the #MeToo wave, in particular by suggesting that it is a re-branded version of the feminist movement that is helpful but not sufficient to address street sexual harassment. Second, the paper outlines how street sexual harassment harms women. Third, some contextual analysis of why governments and legal systems have been slow to address street sexual harassment are provided. Fourth, the paper assesses the various areas of the law that may be used to curb street sexual harassment. Finally, this paper canvasses the ways other governments have taken action against street sexual harassment. Ultimately, this paper argues that the lack of protection of the basic civil right to use the public sphere free of sexual harassment is a failure of the Canadian justice system, and a criminal response remains essential. Other methods of legal regulation are inadequate without the social condemnation that criminal law carries.